Description of the Questionnaire on Perceived Parental Acceptance-Rejection (Annual of the Faculty of Philosophy in Skopje, 2025)
Many psychological theories describe the connection between parental behaviourand children and the character traits that develop in them. One of the most prominenttheories is Rohner’s Parental Acceptance Rejection Theory (PART). He is the author of severaltests describing interpersonal acceptance/rejection between parents and children, parentsand their parents, the perception of the parents themselves and their way of parenting,etc. In his manual he presents the original metric characteristics of the tests measuring theperception of acceptance or rejection.The aim of this paper is to describe the instruments that measure the child’s perceptionof parental acceptance-rejection, as well as the metrical characteristics obtained inthe tests, adapting them to the Macedonian population. The questionnaires were given to 96children and 192 parents. The following instruments were adapted: PARQ for children,PARQ for parents, PARQ for adults, PARQ for intimate partners. The following metric characteristicsof the tests have been obtained: Cronbach Alpha of PARQ for children for themother is .906, for the father .93; Cronbach Alpha of PARQ for parents amounts to .823 forthe mother, while for the father it is .81, Cronbach Alpha of PARQ for adults for assessmentof the mother is .91, while for the father it is .90. Accordingly, there are indications thatthese instruments could be used for the Macedonian population for research purposes, butalso in the clinical practice after the appropriate standardization procedures are implemented.
Keywords: DESCRIPTION OF THE INSTRUMENT; QUESTIONNAIRES OF PARENTAL ACCEPTANCE-REJECTION; PARQ FOR CHILDREN; PARQ FOR PARENTS; PARQ FOR ADULTS